Taxonomic updates in Anthurium sect. Pachyneurium (Araceae) from the Brazilian Atlantic Forest - Camelo, Mel C.; Temponi, Lívia G.; Coelho, Marcus A. N.; Baumgratz, José F.a. (Phytotaxa, 2023)
We present taxonomic updates of Anthurium sect. Pachyneurium, A. pluricarinatum, and an amendment to the description of A. leonii. An identification key for the new species and related taxa from Brazilian Atlantic Forest are included, as well as notes about morphological characters, distribution maps and illustrations are provided.